2021
DOI: 10.1002/brb3.2021
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and behavioral changes in older adults during cognitively demanding dual tasks

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 65 publications
(151 reference statements)
2
36
1
Order By: Relevance
“…For what concerns the motor assessment, results not only highlight the difficulty in performing a curvilinear task with respect to a linear task, but also that there is a further decrement in the gait performance in the DT condition (Figure 3d-g). Several studies have shown a strong relationship between poor executive functioning and slower gait speed, especially during dual tasks that involve a challenging locomotor component [21,23,32]. In our study, curved walking challenged motor control mechanisms more than straight walking [18]: Along curvilinear trajectories, in fact, healthy young adults reduced their walking speed (Table 2), confirming that human subjects adapt their velocity to the radius of the curvature that they are following, with the velocity that tends to decrease when the trajectory becomes more curved [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…For what concerns the motor assessment, results not only highlight the difficulty in performing a curvilinear task with respect to a linear task, but also that there is a further decrement in the gait performance in the DT condition (Figure 3d-g). Several studies have shown a strong relationship between poor executive functioning and slower gait speed, especially during dual tasks that involve a challenging locomotor component [21,23,32]. In our study, curved walking challenged motor control mechanisms more than straight walking [18]: Along curvilinear trajectories, in fact, healthy young adults reduced their walking speed (Table 2), confirming that human subjects adapt their velocity to the radius of the curvature that they are following, with the velocity that tends to decrease when the trajectory becomes more curved [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, the Geriatric Depression Scale (GDS) with scores of 0-30 and Falls E cacy Scale-International (FES-I) with scores of 14-64 were used to assess depression and fear of falls, respectively, 25,26 which can affect the dual-task performance in older adults (i.e., higher scores indicate negative effects). 10 Retrospective falls within 6 months were also collected. The subjects' preferred treadmill walking speed was measured rst by applying an initial speed of 2.0 km/h and adding increments of 0.1 km/h, then by decreasing the speed from 6.5 km/h, which was con rmed with previous ndings.…”
Section: Methodsmentioning
confidence: 99%
“…1,8 The negative effects of aging (motor and cognition) have caused excessive PFC activation, which was compensatory mechanism indicating over-recruitment of cognitive resources and reduced e ciency of PFC. 3,9,10 Furthermore, since aging-related changes in the PFC occur rapidly, 5 we considered that neural mechanisms in dual-task performance may differ between older and younger adults. However, some brain imaging studies have shown less PFC activation in older adults during dual-tasking, with condition factors (overground and treadmill walking set-ups) and age considered as factors possibly causing these con icting ndings.…”
Section: Introductionmentioning
confidence: 99%
“…Each cognitive task was programmed in E-Prime software (Psychology Software Tools, Pittsburgh, PA). The cognitive tasks described below have been used in published dual-task studies (Fraser et al, 2016 ; Lajoie et al, 2016 ; St-Amant et al, 2020 ; Salzman et al, 2021 ). Moreover, the discrete tasks were made up of a simple reaction time (SRT) and go/no-go inhibition task (GNG) whereas the continuous tasks were composed of n-back (NBK) and double number sequence (DNS) working memory tasks.…”
Section: Methodsmentioning
confidence: 99%
“…This statistical approach allows us to assess if there are discrete vs. continuous task differences, if there are dual vs. single task differences (i.e., SM vs. DT or SC vs. DT), any hemispheric differences, and if there are any interactions with these factors. In addition, we have applied this approach to a completed study with the exact same design, tasks, and protocols but was conducted with older adults (Salzman et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%